Characterization of the bonding zone in AZ91/AlSi12 bimetals fabricated by liquid-solid compound casting using unmodified and thermally modified AlSi12 alloy - Mola, Renata (Strojniški vestnik, 2020)
Liquid-solid compound casting was used to produce two types of AZ91/AlSi12 joints. The magnesium alloy was the cast material poured onto a solid aluminium alloy insert with an unmodified or modified structure. The bonding zone obtained for the unmodified insert was not uniform in thickness. There was a eutectic region (Mg17Al12 + a solid solution of Al in Mg) in the area closest to the AZ91. The region adjacent to the AlSi12 had a non-uniform structure with partly reacted Si particles surrounded by the Mg2Si phase and agglomerates of Mg2Si particles unevenly distributed in the Mg-Al intermetallic phases matrix. Cracks were detected in this region. In the AZ91/AlSi12 joint produced with a thermally modified AlSi12 insert, the bonding zone was uniform in thickness. The region closest to the AZ91 alloy also had a eutectic structure. However, significant microstructural changes were reported in the region adjacent to the modified AlSi12 alloy. The microstructure of the region was uniform with no cracks; the fine Mg2Si particles were evenly distributed over the Mg-Al intermetallic phase matrix. The study revealed that in both cases the microhardness of the bonding zone was several times higher than those of the individual alloys; however, during indenter loading, the bonding zone fabricated from modified AlSi12 alloy was less prone to cracking.
Keywords: aluminijeva zlitina; aluminium alloy; compound casting; grain refinement; magnesium alloy; magnezijeva zlitina; microhardness; microstructure; mikrostruktura; mikrotrdota; sestavljeno litje; udrobnjenje